2019
DOI: 10.1111/jth.14521
|View full text |Cite
|
Sign up to set email alerts
|

The scavenger receptor SCARA5 is an endocytic receptor for von Willebrand factor expressed by littoral cells in the human spleen

Abstract: Background: Scavenger receptors play a significant role in clearing aged proteins from the plasma, including the large glycoprotein coagulation factors von Willebrand factor (VWF) and factor VIII (FVIII). A large genome-wide association study metaanalysis has identified genetic variants in the gene SCARA5, which encodes the class A scavenger receptor SCARA5, as being associated with plasma levels of VWF and FVIII.Objectives: The ability of SCARA5 to regulate the clearance of VWF-FVIII was characterized.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…17 Recently, it was shown that the macrophage galactose-type lectin receptor also regulates VWF clearance in a sialic acid-dependent manner. 18 In addition, several other specific lectin receptors (including sialic acid-binding immunoglobulin-like Lectin 5 19 and C-type lectin domain family 4 member M) 20 and scavenger receptors (including low-density lipoprotein receptor-related protein-1, 21 scavenger receptor A1, 22 scavenger receptor class A member 5, 23 and stabilin-2) 24 have been shown to participate in VWF clearance.…”
Section: Vwf Clearancementioning
confidence: 99%
“…17 Recently, it was shown that the macrophage galactose-type lectin receptor also regulates VWF clearance in a sialic acid-dependent manner. 18 In addition, several other specific lectin receptors (including sialic acid-binding immunoglobulin-like Lectin 5 19 and C-type lectin domain family 4 member M) 20 and scavenger receptors (including low-density lipoprotein receptor-related protein-1, 21 scavenger receptor A1, 22 scavenger receptor class A member 5, 23 and stabilin-2) 24 have been shown to participate in VWF clearance.…”
Section: Vwf Clearancementioning
confidence: 99%
“…16,17 Confirmatory studies using animal models, cell-based studies, and ligand-receptor binding assays have confirmed that CLEC4M, SCARA5, and stabilin-2 are capable of binding and internalizing the human VWF protein or the VWF-FVIII complex. [18][19][20] Variants in these receptors may therefore modify the PK profile of FVIII.…”
Section: Introductionmentioning
confidence: 99%
“…SCARA-5 was co-localized with VWF and can bind and internalize this factor alone or in a complex with FVIII. The binding and internalization of FVIII to SCARA-5 cannot occur in the absence of VWF [142]. SCARA-5 is expressed by osteoblastic like cells and inhibits their proliferation [143].…”
Section: Scavenger Receptor Class a Member 5 (Scara-5)mentioning
confidence: 99%